Local Left Ventricular Epicardial J Waves and Late Potentials in Brugada Syndrome Patients with Inferolateral Early Repolarization Pattern - Nagase, Satoshi; Tanaka, Masamichi; Morita, Hiroshi; Nakagawa, Koji; Wada, Tadashi; Murakami, Masato; Nishii, Nobuhiro; Nakamura, Kazufumi; Ito, Hiroshi; Ohe, Tohru; Kusano, Kengo F. (Frontiers in Physiology, 2017)
Background: Brugada syndrome (BrS) is characterized by J-point or ST-segment elevation on electrocardiograms (ECGs) and increased risk of ventricular fibrillation (VF). In BrS, epicardial depolarization abnormality with delayed potential on the right ventricular outflow tract is reportedly the predominant mechanism underlying VF. Yet VF occurrence is also associated with early repolarization (ER) pattern in the inferolateral ECG leads, which may represent the inferior and/or left lateral ventricular myocardium. The aim of this study was to examine epicardial electrograms recorded directly at the left ventricle (LV) in BrS patients after VF episodes. Methods: In 12 BrS patients who had experienced VF episodes and 17 control subjects, a multipolar catheter was introduced into the left lateral coronary vein for unipolar and bipolar electrogram recordings at the LV epicardium. Both inferior and lateral ER patterns on ECG were observed in three BrS patients and six control subjects. Results: In the epicardium, prominent J waves were detected using unipolar recording, and potentials after the QRS complex were detected using bipolar recording in three of the 12 BrS patients. These three patients also showed both inferior and lateral ER patterns on ECG. Neither prominent J waves nor potentials after the QRS complex were recorded at the endocardium of the LV in any of these three patients; nor were they seen at the epicardium in any of the control subjects. These features were accentuated on pilsicainide administration (n = 2) but diminished on constant atrial pacing (n = 3) and isoproterenol administration (n = 1). The J waves observed through unipolar recording coincided with the potentials after QRS complex observed through bipolar recording and with the inferolateral ER patterns on ECG. Conclusions: We recorded prominent J waves in unipolar electrogram and potentials after QRS complex in bipolar electrogram at the LV epicardium in BrS patients with global ER pattern. The prominent J waves coincided with the potentials after QRS complex and the inferolateral ER pattern on ECG. The characteristics of the inferolateral ER pattern on ECG in these patients primarily represent depolarization feature.